Organization for Economic Cooperation and Development. Technical Change and Economic Policy. París, 1980. 117 p. - Hodara B., Joseph (Estudios Demográficos y Urbanos, 1981)
Organization for EconomicCooperation and Development, Technical Change and Economic Policy, París, 1980.